2022
DOI: 10.1007/s13399-022-02431-2
|View full text |Cite
|
Sign up to set email alerts
|

Parametric optimization and kinetic modelling for organic matter removal from agro-waste derived paper packaging biorefinery wastewater

Abstract: state-of-the-art paper packaging biorefinery utilizes cellulose fibrous material from paddy straw and papaya latex to produce packaging products. This in turn generate wastewater with high organic matter content that if disposed without treatment, will pollute water bodies, and affect aquatic life below water. Therefore, to comply with "clean water and sanitation" (SDG 6) and "life below water" (SDG 14), this study assesses the efficacy of an extended aeration activated sludge (EAAS) in the treatment of paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…The effects of PCP load on COD, NH 3 -N, and PCP removals were studied in a bioreactor treating recycled paper wastewater [142]. The bioreactor's stability and performance at various PCP loads suggest that joining biofilm and granular activated carbon (GAC) in the treatment under severe organic load variations could be beneficial.…”
Section: Chlorophenolsmentioning
confidence: 99%
“…The effects of PCP load on COD, NH 3 -N, and PCP removals were studied in a bioreactor treating recycled paper wastewater [142]. The bioreactor's stability and performance at various PCP loads suggest that joining biofilm and granular activated carbon (GAC) in the treatment under severe organic load variations could be beneficial.…”
Section: Chlorophenolsmentioning
confidence: 99%
“…Catalysts 2022, 12, x FOR PEER REVIEW 2 of 14 [11]. Recent studies have shown that the bioaugmented biofloc efficiently purifies water, but the mechanism is not clearly described, in particular, the EPS synthesis [12][13][14].…”
Section: Changes In Eps Content In the Bioflocmentioning
confidence: 99%
“…They adhere to bacteria, fungi, algae, protozoa, and organic polymers, forming structurally diverse flocs using secreted extracellular polymer substances [9]. OBF removes ammonium nitrogen, total nitrogen, and total phosphorus from water through microbial assimilation and nitrification [10] and removes organic matter from water through biological adsorption [11]. Recent studies have shown that the bioaugmented biofloc efficiently purifies water, but the mechanism is not clearly described, in particular, the EPS synthesis [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…2015; Jagaba et al . 2022). Accumulation of metal ions in wastewater can be effectively reduced by using nanomaterials as adsorbent (Jagaba et al .…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterial-mediated treatment methodologies are being studied to treat wastewater which targets significant contaminants like nitrate, phenols, total organic compounds (Azari et al 2014;Jalili Naghan et al 2015;Jagaba et al 2022). Accumulation of metal ions in wastewater can be effectively reduced by using nanomaterials as adsorbent (Jagaba et al 2020;Saeed et al 2021).…”
Section: Introductionmentioning
confidence: 99%